Survey of Sandy Beaches on the Syrian Coast: Extension, Coloration, Mineral Composition, and Granular Structure - Ibrahim, Amir; Fadel, Ikbal (Latakia University Journal -Biological Sciences Series, 2024)
Sandy beaches were surveyed along the Syrian coast, and their locations, extensions, colors, mineral composition, and granular structure were determined. It was found that ~90.93km of sandy beaches exists along the Syrian coast: including ~74.47km of large stretches (>5km), distributed between Al Badrusiyah-Al Basit (5.5km), Al Shaqifat (12.6km), Baniyas-Tartus (22km), and South of Tartous (34.37km). In addition, there are 13.2km of medium extensions (1-5 km), distributed between Umm Al Tuyur (2.5km), Wadi Qandil (1.8km), Blue Beach (1.25km), Marsa Al Khoder (4.15km), Al Khrab Town (1km), and North of Baniyas (2.5km). Above that, there are 3.26km of short extensions (<1km) in 16 locations distributed between the Al Samra and Ibn Hani regions. Sand dunes were recorded in Al-Shaqifat and Al-Hamidiyeh beaches. Black sand of volcanic origin dominates Al Badrosiyah, Ras Al Basit, Thermal Station, Burj Al Sabi, and Al Kharab. This black sand mixes with the golden sand in Umm Al Tuyour, Wadi Qandil, and Al Kharaba. Golden sand reappears in the Golden Sand Resort, Al Ahlam Beach, Al Mantar, and Al Hamidiya. Calcite mineral formed large percentages of the samples from 8 locations, followed by Quartz in 6 locations, then by Augite in 4 locations and Dolomite in only 2 locations. Other minerals (Argonite, Feldspar, Serpentine and Amphibole) constituted small variable percentages. In most of the studied areas, the granular structure of sand samples is characterized by a scarcity of medium-sized and coarse sands, compared to a variable and clear dominance of fine and very fine sands and silt of various sizes.